Effectiveness and cost effectiveness of daily all over body application of emollient during the first year of life for preventing atopic eczema in high risk children (The BEEP trial): protocol for a randomised controlled trial - Chalmers, J.R.; Haines, Rachel H.; Mitchell, Eleanor J.; Thomas, Kim S.; Brown, Sara J.; Ridd, Matthew; Lawton, Sandra; Simpson, Eric L.; Cork, Michael J.; Sach, Tracey H.; Bradshaw, Lucy E.; Montgomery, Alan A.; et al. (BioMed Central, 2017)
Background: Atopic eczema (AE) is a common skin problem that impairs quality of life and is associated with the development of other atopic diseases including asthma, food allergy and allergic rhinitis. AE treatment is a significant cost burden for healthcare providers. The purpose of the trial is to investigate whether daily application of emollients for the first year of life can prevent AE developing in high risk infants (first degree relative with asthma, AE or allergic rhinitis).